The cell in the ink: Improving biofabrication by printing stem cells for skeletal regenerative medicine. (July 2019) - Cidonio, G.; Glinka, M.; Dawson, J.I.; Oreffo, R.O.C.
Abstract: Recent advances in regenerative medicine have confirmed the potential to manufacture viable and effective tissue engineering 3D constructs comprising living cells for tissue repair and augmentation. Cell printing has shown promising potential in cell patterning in a number of studies enabling stem cells to be precisely deposited as a blueprint for tissue regeneration guidance. Such manufacturing techniques, however, face a number of challenges including; (i) post-printing cell damage, (ii) proliferation impairment and, (iii) poor or excessive final cell density deposition. The use of hydrogels offers one approach to address these issues given the ability to tune these biomaterials and subsequent application as vectors capable of delivering cell populations and as extrusion pastes. While stem cell-laden hydrogel 3D constructs have been widely established in vitro, clinical relevance, evidenced by in vivo long-term efficacy and clinical application, remains to be demonstrated. This review explores the central features of cell printing, cell-hydrogel properties and cell-biomaterial interactions together with the current advances and challenges in stem cell printing. A key focus is the translational hurdles to clinical application and how in vivo research can reshape and inform cell printing applications for an ageing population. Graphical abstract: Cell printing - capacity and limitations. Cell type and density are important factors in the printing of living cells. Post-printing consequences including: (i) impaired cell proliferation, (ii) maintenance of phenotype and genotype, (iii) preservation of cell integrity and morphology are issues that need to be considered. Stem cell printing aims to deposit cells in three dimensions within an environment conducive to proliferation and differentiation. Therefore, long-term investigations of cell viability and proliferation in vitro and in vivo are required to elucidate construct maturation and effective tissue regeneration and integration. Importantly, the properties of the hydrogel cell carrier (biocompatibility, bioactivity, physical characteristics) for the select 3D print approach envisaged are crucial for cell encapsulation, protection and support during differentiation and proliferation.Image 1